Video Spectral Methods and Tools for Monitoring of Controlled Parameters of Forest Fires and Oil Spill Accidents - A. S. Sizikov; Y. V. Belyaev; I. M. Tsykman; A. P. Popkov (Приборы и методы измерений)
The main results of the creation of the domestic complex “Vizir” for measuring bidirectional spectropolarization reflection coefficients and brightness of natural and artificial objects were presented in the article. Its purpose, composition and main technical parameters were indicated.Spectral-polarization studies of the characteristics of samples that simulates objects (pollution) of natural (forest fires) and man-made (oil spills) emergencies were performed with the help of complex “Vizir” using polarizing nozzles under various conditions (angles of illumination, observation, pollution concentration, the time that passed since the contamination, the degree of wood thermal damage). The results of studies made it possible to increase the accuracy of identification of monitoring objects in emergency zones up to two times.The main provisions of the two developed methods were outlined. The first method was methodology for determination of the controlled parameters of forest fires by means of aviation monitoring, which makes it possible to record the maximum values of the degree of polarization of reflected radiation for coal 30–40 % and for semi-coal 15–20 % in the wavelength range from 0.5 to 0.7 μm. The second one was methodology for determination of the controlled parameters of man-made emergencies with oil spills by means of aviation monitoring, which makes it possible to record the maximum values of the degree of polarization of an oil spill on water: 40–50 % at optimal view angles close to specular in relation to the angle of solar radiation incidence.The developed methods were introduced into the activities of the Ministry for Emergency Situations of the Republic of Belarus to make the right management decisions to eliminate emergency situations and their consequences.